Pelatihan Angklung Dalam Upaya Menumbuhkan Cinta Budaya Indonesia di Sanggar Alang-Alang Surabaya - Nistah, Anjelina; Lestari, Gunarti Dwi (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan UNESA, 2024)
Training is a part of education that involves the acquisition and enhancement of skills outside the education system in a relatively short time by prioritizing practice. Angklung is one of the performing arts that is the pride of the Indonesian people, especially the people of West Java (and Banten). The purpose of this research is to know and describe that fostering children's love of culture can be through a simple way, namely with angklung training at Sanggar Alang-Alang Surabaya. The research method used is descriptive qualitative with data collection techniques through interviews, observation, and documentation. Data analysis techniques include data collection, data reduction, data presentation, and verification or conclusion drawing. The results of this study indicate that fostering love of culture can be through a simple way by participating in angklung training at the alang-alang Surabaya studio by providing material for students to memorize folk songs. The existence of complete angklung facilities is a supporting factor for students to be enthusiastic about practicing angklung. Keywords: Angklung Training, Cultivating Love for Indonesian Culture